PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN PAI KELAS IV - Sri Fitri Belina; Asep Usamah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Developing students' critical thinking skills is a crucial part of the classroom learning process. Students can solve difficulties and create logical, coherent, and critical thinking patterns by using these skills in the 21st century. Prioritizing problem-solving in the classroom helps students better understand and remember concepts and knowledge, ultimately improving learning outcomes. Unfortunately, many current teaching methods are still teacher-centered, which makes students obedient, easily distracted, or even distracted in class. This study aims to assess the effects of the Problem-Based Learning (PBL) paradigm on fourth-grade Islamic Religious Education (PAI) students' critical thinking abilities. A Nonequivalent Control Group Design, a quasi-experimental design, was employed in conjunction with a quantitative experimental approach for the goals of this investigation. The analysis's findings indicate that the Problem-Based Learning (PBL) model is a great tool for enhancing students' critical thinking abilities, which makes it a perfect fit for the classroom.